2022
DOI: 10.1136/bmjopen-2021-053722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, risk factors and outcomes of pediatric COVID-19: a retrospective cohort multicentre study in Saudi Arabia

Abstract: ObjectiveTo describe the risk factors, clinical profile and outcomes of COVID-19 in the paediatric population.DesignMulticentre, retrospective observational study.SettingFour tertiary hospitals in Saudi Arabia.PatientsWe recruited 390 paediatric patients aged 0–18 years who presented from March to December 2020 and tested positive for COVID-19 on PCR.Main outcome measuresWe retrospectively analysed medical records for sociodemographics, health indicators, clinical presentations, laboratory findings, clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
2
14
1
1
Order By: Relevance
“…This lower tendency to accept the vaccine in younger children may be attributed to the higher parental perceived risk versus benefit in this age group. This is comparable to the literature that showed that the COVID-19 course is more severe in both infants and teenagers [ 28 , 29 , 30 ]. Among 57 studies with 21,549 patients that were included in the meta-analysis, Harwood et al found that compared with children aged one to four years, infants had increased odds of admission to critical care and death.…”
Section: Discussionsupporting
confidence: 90%
“…This lower tendency to accept the vaccine in younger children may be attributed to the higher parental perceived risk versus benefit in this age group. This is comparable to the literature that showed that the COVID-19 course is more severe in both infants and teenagers [ 28 , 29 , 30 ]. Among 57 studies with 21,549 patients that were included in the meta-analysis, Harwood et al found that compared with children aged one to four years, infants had increased odds of admission to critical care and death.…”
Section: Discussionsupporting
confidence: 90%
“…These cases featured in Literature during the first pandemic waves when severe forms of diseases in children were also registered, with an incidence rate of approximately 1 to 5000 cases of COVID-19 [ 14 , 35 ]. The first cases were documented in USA and Italy, both in previously healthy children as well as in those with comorbidities [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Age groups were determined based on the World Health Organization Guideline on “COVID-19 disease in children and adolescents.” 12 The clinical severity was determined using the classification system proposed by Dong et al and summarized in Table 1 . 13 14 15 16 17 The medical records of parents and siblings were investigated and the source of infection was determined as a household contact if the SARS-CoV-2 RT-qPCR test of a household contact was positive within 5 days' of the case.…”
Section: Methodsmentioning
confidence: 99%